Efficiency of Resistant Starch and Dextrins as Prebiotics: A Review of the Existing Evidence and Clinical Trials - Włodarczyk, Michał; Śliżewska, Katarzyna (Nutrients, 2021)
In well-developed countries, people have started to pay additional attention to preserving healthy dietary habits, as it has become common knowledge that neglecting them may easily lead to severe health impairments, namely obesity, malnutrition, several cardiovascular diseases, type-2 diabetes, cancers, hypertensions, and inflammations. Various types of functional foods were developed that are enriched with vitamins, probiotics, prebiotics, and dietary fibers in order to develop a healthy balanced diet and to improve the general health of consumers. Numerous kinds of fiber are easily found in nature, but they often have a noticeable undesired impact on the sensory features of foods or on the digestive system. This led to development of modified dietary fibers, which have little to no impact on taste of foods they are added to. At the same time, they possess all the benefits similar to those of prebiotics, such as regulating gastrointestinal microbiota composition, increasing satiety, and improving the metabolic parameters of a human. In the following review, the evidence supporting prebiotic properties of modified starches, particularly resistant starches and their derivatives, resistant dextrins, was assessed and deliberated, which allowed drawing an interesting conclusion on the subject.